(untitled) (Revista Ciência Agronômica, 2015)
The aim was to evaluate the effects of grazing height of Brachiaria ruziziensis on the production of straw, and the establishment and grain yield of a soybean crop, under an integrated crop-livestock system, on a typic dystrophic Red Latosol at the Experimental Farm of the Agronomic Institute of Paraná (IAPAR), in Xambrê, in the state of Paraná, Brazil (PR). The study was carried out between September of 2010 and April of 2012. The experimental design was of randomised blocks, in lots split over time, with five treatments and three replications. The following were determined for the Brachiaria ruziziensis: shoot dry matter weight, plant residue dry matter weight, and total dry matter weight (Brachiaria ruziziensis shoot weight + plant residue weight). Also determined were variables related to the yield of the soybean crop (number of plants per metre, plant height and grain productivity), for the crop years 2010/2011 and 2011/2012. Straw production is greater in areas of Brachiaria ruziziensis where there is no grazing compared to areas where grazing occurs; the high production seen in areas with greater grazing heights should also be noted. The final number of plants, plant height and productivity in the soybean were not affected by the grazing height of the Brachiaria ruziziensis.